Experimental Study on Preparation of Straw Activated Carbon by Microwave Heating. (2017) - Yang, Dong; Jiang, Lihui; Yang, Shanglin; Wei, Shijun
Abstract: Activated Carbon (AC) is amorphous carbon which was obtained through carbonaceous material. AC has a large specific surface area, so it has good adsorption capacity for inorganic substances, organic substances and colloidal particles in the gas or solution. Annual consumption is huge. Corn stalks are the remnants of agricultural production. China is one of the countries with the largest straw production in the world, but straw has not been fully utilized for a long time. A large number of straws were discarded or burned, which will waste resources and cause environmental pollution. Corn stalks were selected as raw material, pyrophosphoric acid was selected as activator, and microwave irradiation method was used to study the preparation technology of corn stalk based activated carbon in this paper. The optimum conditions for the preparation of AC from corn stalks were determined by the orthogonal experiment. The optimum parameters for the preparation of AC by microwave heat activation in the laboratory stage were obtained. The concentration of pyrophosphate was about 45% (wt), the impregnation ratio was 1: 2, the impregnation time was 8 hours, the radiant power was 400W, and the activation time was 8 minutes.